Three new species of the genus Boulenophrys (Anura, Megophryidae) from southern China - Qi, Shuo; Lyu, Zhi-Tong; Wang, Jian; Mo, Yun-Ming; Zeng, Zhao-Chi; Zeng, Yang-Jin; Dai, Ke-Yuan; Li, Yuan-Qiu; Grismer, L. Lee; Wang, Ying-Yong (Zootaxa, 2021)
The diversity of Asian horned toads is considered highly underestimated and to contain a large number of undescribed cryptic species. In this work, we describe three new species of Boulenophrys from south China, namely, Boulenophrys yaoshanensis sp. nov. from central Guangxi, Boulenophrys yingdeensis sp. nov. from northern Guangdong, and Boulenophrys yunkaiensis sp. nov. from western Guangdong. These three new species can be distinguished from all recognized congeners by a combination of morphological characteristics and significant genetic divergences. These descriptions increase the number of recognized species of Boulenophrys to 61. In addition, an updated checklist of the Asian horned toads of the subfamily Megophryinae is provided in this study.